Tauhid dalam Perspektif Rabi’ah Addawiyah - Syarboini Syarboini (Saree : Research in Gender Studies, 2021)
Along with the times, it is very important for the soul and every Muslim to be able to defend the faith and religion of Islam, especially with the various events that occur in society that show deviations in it from monotheism education such as shirk, believing in myths and even being willing to sacrifice religion. in order to obtain positions and positions. Rabi'ah Al Adawiyah was very obedient to Allah, the power of monotheism made her faith so strong, even though the trials she experienced were so heavy, the two Rabi'ahs paid attention to the behavior of zuhud, worship, and her love for Allah after she was released from slavery. Third, Rabi'ah Al Adawiyah is a very pious guardian. How often tears flow because of sadness and love for him. And the four Rabi'ah Al Adawiyah are the founders of the school of love, Rabi'ah finds true life is by loving Allah.